Feasibility of a brief mindfulness-based program for burnout in pain healthcare professionals - Server, Anna; Suso-Ribera, Carlos; Pérez-Carrasco, Marcos; Medel, Javier; Mesas, Ángela; Ayora, Alfonso; Gracia, Rosa Maria (Frontiers in Psychology, 2022)
Introduction Stress inherent to health care, which is characterized by work overload and shortage of specialized staff, is associated with decreased quality of life and suboptimal patient care. Mindfulness-based programs have proved to be effective in reducing stress in healthcare providers. This study aims to assess the feasibility of an 8-week mindfulness program to reduce the burnout levels of the staff of a pain clinic in a tertiary public hospital. Materials and methods A longitudinal study with a within subject pre/post-intervention design, consisting of daily face-to-face 10-min sessions and the creation of a virtual group using a social media platform. Variables measured: burnout, mindfulness, empathy, self-compassion, and demographic characteristics. Results Program feasibility (i.e., reach, adherence, acceptability, and preliminary effectiveness) was evaluated in 10 participants (6 physicians, 2 nurse practitioners, 1 nursing assistant, and 1 administrative). The results revealed a high reach (i.e., participation rate of 90%), excellent adherence to the program (daily practice 95% of times), and very good acceptability of the group format and satisfaction with most treatment components. Regarding potential effectiveness, we report the results of the Wilcoxon signed-rank tests and its associated effect size (r). We observed improvements in mindfulness and all its subscales (−2.077 ≤ Z ≤ −2.703, 0.69 ≤ r ≤ 0.90, all p < 0.05) except for non-reactivity and all subcomponents of self-compassion (−2.501 ≤ Z ≤ −2.611, 0.83 ≤ r ≤ 0.87, all p < 0.05) but not on its global self-compassion score. Empathy and burnout did not change. In an exploratory manner, however, we found significant reductions in the burnout component of emotional exhaustion, but only in physicians (Z = −2.201, p = 0.028, r = 0.73). Discussion We believe that the 8-week mindfulness-based program described in the present investigation might be a feasible and potentially effective method that can be easily implemented to reduce burnout and promote mindfulness in specialized pain clinics.